Anti-inflammatory and anti-obesity activity of endophytic fungal isolates of Nardostachys jatamansi - Neha Kapoor; Madeha Farooq
The present study underpins the anti-obesity and anti-inflammatory activity of fungal endophytes inhabiting Nardostachys jatamansi of the high-altitude region of Uttarakhand. The study entails the recovery of 15 endophytic fungi from the leaves, inflorescence, and stem of N. Jatamansi, showing maximum colonisation in plant leaves. The anti-obesity and anti-inflammatory potential of the isolates was investigated via phenol red plate assay, L-asparaginase production, and albumin denaturation assay. The maximum albumin denaturation inhibitory activity of 74.8% was observed in -22JTM(I), followed by 70.3 and 67.6% in -6(b)JTM(L) and-7JTM(S), respectively. Three isolates were found to demonstrate potent L-asparaginase production, viz. -22JTM(I),-7JTM(S) and -25JTM(I). Interestingly, partial purification of the L-asparaginase demonstrated maximum enzyme production in -22JTM(I). In the phenol red plate assay, six isolates demonstrated anti-obesity activity, of which four isolates viz, -6(b)JTM (L), -7JTM (S), -23JTM (I) and -25JTM (I) exhibited 100% lipase inhibitory action. The free radical scavenging potential of the isolates as a contributor to the observed bioactivities was investigated. The isolates exhibited potent antioxidant activity with 70.9% by -23JTM (I) followed by -14JTM (L) and -22JTM (I) with 67.4 and 60.1%, respectively. The most potent isolate, -22JTM (I), was identified as Fusarium sp. by morpho-taxonomic tools. The present study showcases the promising therapeutic potential of fungal endophytes from N. jatamansi, demonstrating the repository of potent anti-obesity and anti-inflammatory chemistries.